Nutritional status and dietary habit of COVID-19 patients: A study in a tertiary hospital - Eva, Moushumi Afrin; Haque, Fahim; Begum, Nasreen; Kabir, A S M Anwarul; Yasmeen, B H Nazma (Northern International Medical College Journal, 2024)
Background: Nutritional status has impact on body immune function that is important for controlling disease process and prognosis of the newly emerging Coronavirus Disease 2019 (COVID-19). As no vaccine or specific antiviral treatment is not available for COVID-19, therefore, improvement of nutritional status is important. Adequate and appropriate diet is required for maintaining good nutritional status. There is very few research carried out to evaluate the influence of nutritional status and dietary habit of patients with COVID-19. Objective: To study the nutritional status and dietary habit of COVID-19 patients admitted in a tertiary hospital of Dhaka, Bangladesh and its impact on the severity of the disease COVID-19. Methodology: A cross-sectional study was performed on 384 patients in the Corona unit of Holy Family Red Crescent Hospital during 17th May to 31st December’ 2020. Patients were selected conveniently according to inclusion criteria. COVID-19 patients were categorized as Mild, Moderate and Severe cases according to National Institute of health and latest Public Health Information from Centers for Disease Control (CDC). Direct interviewing of the selected patients with pretested structured questionnaire, data were collected on socio demographic characteristics, nutritional status following Body Mass Index (BMI) grading, daily consumption of different food items in the last 3 months and dietary habits in the last 3 months of these three categories of patients. Written consent of the patient and ethical clearance was obtained prior to data collection. All statistical analyses were performed by using the SPSS software version 21. Result: A total of 384 patients interviewed. Age distribution was Mean ±SD, 42.85±13.82. Male/Female ratio 1.33. Most of them were graduates, 33.1% and 42.9% were Govt. service holders. Monthly family income was Tk 35000 (taka thirty-five thousand) and above in 39.6% cases. Regarding source of infection in these patients, 40.3% and 35.2% from traveling abroad and shopping respectively. Urban dwellers were75% and 25% from rural area. Nutritional status of COVID-19 patients was calculated according to BMI grading. Among all Underweight COVID-19 patients- 90% were Moderate cases. Among all Normal nutritional status COVID- 19 patients we found 37.5%, 41.7% and 20.8% were in mild cases, moderate cases, and severe cases respectively. Regarding Overweight COVID-19 patients we found 46.7% and 32.7% in moderate and in severe cases. Obese 1 were 48.1% in moderate cases and 32.1% in severe cases of COVID-19 patients. On the other hand, all (100%) obese 2 patients were moderate cases. BMI found statistically significant p – 0.002. Regarding food items protein showed statistically significant (p- 0.04). In severe cases having good sun exposure was found in only 19.5% cases. Regarding dietary habit of COVID-19 patients, most of the variables were found statistically significant i,e skipping of their meal (p-0.016), number of meal ( p-0.040), quality of food( p-0.014), taking food according to daily requirement ( p - 0.021) and eating extra salt with food(p-0.029). Conclusion: Considering the result, it can be concluded that COVID-19 patients were mostly middle aged from urban areas with average economic status. Source of infection was from traveling abroad and shopping. Nutritional status of most of Moderate and Severe COVID-19 cases were under weight, obese 1 and obese 2. Concerning diet and dietary habit, protein, skipping of meal, number of meals, variety of food, eating food according to daily requirement and eating extra salt with food significantly associated with the severity of COVID-19. This was a single centered study with a small sample size. A multicenter, larger sample size study recommended for confirming our data and to get an actual view of the nutritional status and dietary habit of COVID19 patients. Northern International Medical College Journal Vol. 13 No. 1-2 July 2021-January 2022, Page 574-580